2021
DOI: 10.1186/s41077-021-00158-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of virtual reality and augmented reality to enhance cardio-pulmonary resuscitation: a scoping review

Abstract: Background and objective Virtual reality (VR) and augmented reality (AR) have been proposed as novel methods to enhance cardio-pulmonary resuscitation (CPR) performance and increase engagement with CPR training. A scoping review was conducted to map the global evolution of these new approaches to CPR training, to assess their efficacy and determine future directions to meet gaps in current knowledge. Methods A standardised five-stage scoping method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…That is in line with a recent review that evaluated VR to improve CPR training, which concluded that this field was both diverse and immature. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is in line with a recent review that evaluated VR to improve CPR training, which concluded that this field was both diverse and immature. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] A new field to study is the evaluation of CPR education in laypersons, as limited high-quality data from very heterogeneous designed studies prone to biases exist. [ 13 ] Therefore, CPR education research shall not only limit their focus on educational outcomes and results, but equal efforts need to be made to investigate education strategies that lead to improved patient outcomes after a cardiac arrest, which is still the highest priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates it is convenient, engaging, and interactive [ 10 ]. VR has been shown to be effective across a range of healthcare settings and has the potential to deliver crucial empathy-building learning for frontline mental health staff due to its immersiveness, which provides direct and realistic, first-hand experiences [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) technology designed to maximise immersion has been shown to be able to overcome these limitation s[ 6 ]. Nas et al reported a comparable chest compression rate but inferior compression depth with VR CPR training compared to conventional face-to-face training [ 7 ].…”
Section: Introductionmentioning
confidence: 99%